A cell isolation method from Ligusticum chuanxiong Hort. suitable for obtaining high-quality RNA for Smart-seq - Ruoshi Li; Mengmeng Wu; Shunlu Chen; Lan Huang; Can Wang; Zhiyin Yu; Feng Huang; Xiaofen Liu; Nianyin Zhu; Chi Song; Guihua Jiang; Xianmei Yin (Plant Methods)
Abstract Purpose To overcome the risk of cellular damage and RNA degradation caused by high temperatures and cellular damage induced by laser capture microdissection (LCM) during plant single cell or small cell cluster isolation, we developed a rapid and simple method for single-cell separation and trace RNA extraction. The extracted RNA can be used for Smart-seq analysis, enabling comprehensive studies of various cell types. Method We used the secretory cells of Ligusticum chuanxiong Hort. fibrous root. First, we performed paraffin embedding to maintain RNA stability, and then examined the optimal slice thickness to obtain intact secretory cells. We compared the RNA quality of secretory cells isolated by LCM versus manual dissection under a microscope with a scalpel. Finally, xylene was introduced into the lysis buffer, followed by rapid shaking to achieve simultaneous dewaxing and cell lysis, and the xylene layer was then removed by centrifugation. Result A slice thickness of $$20\,μ \text {m}$$ 20 μ m best preserved the integrity of secretory cells. Compared with LCM, this method yielded higher quality RNA. The obtained transcriptomic data showed an average Q30 score exceeding 91% and a genome mapping rate surpassing 86%. Conclusion This method can yield high-quality trace RNA suitable for Smart-seq analysis. Moreover, the significant differences in the transcriptomes of various small cell clusters types demonstrate the effectiveness and specificity of our manual dissection method.